2015
DOI: 10.3747/co.22.2636
|View full text |Cite
|
Sign up to set email alerts
|

Quality of End-of-Life Cancer Care in Canada: A Retrospective Four-Province Study Using Administrative Health Care Data

Abstract: BackgroundThe quality of data comparing care at the end of life (eol) in cancer patients across Canada is poor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 33 publications
(44 reference statements)
1
55
0
Order By: Relevance
“…In England, about 46.7% of all deaths occur in hospital (2015 data) with a decrease of 11.2% in 10 years, while in the United States, 28.8% of deaths occurred in hospital for EOL cancer patients in 2003 with a 14.4% decrease in 7 years . Higher rates of cancer patients dying in a hospital are also observed in Canada, where on average 54% patients died in hospital . Location of death not only influences the dying experience but also affects healthcare utilization and costs .…”
Section: Introductionmentioning
confidence: 99%
“…In England, about 46.7% of all deaths occur in hospital (2015 data) with a decrease of 11.2% in 10 years, while in the United States, 28.8% of deaths occurred in hospital for EOL cancer patients in 2003 with a 14.4% decrease in 7 years . Higher rates of cancer patients dying in a hospital are also observed in Canada, where on average 54% patients died in hospital . Location of death not only influences the dying experience but also affects healthcare utilization and costs .…”
Section: Introductionmentioning
confidence: 99%
“…Those outcomes were selected because, in prior studies, a shorter interval from diagnosis to death [16][17][18][19]22,23 and in-hospital death 18,20,21 were indicators of lower rates of access to out-of-hospital palliative support. Other outcome indicators of the quality of community-based palliative care at end of life are timely enrolment in specialized palliative care 16,20,23 , no or few days in hospital in the last month of life 18,22 , and minimal use of the emergency department [18][19][20][21][22] . Receiving palliative radiation [16][17][18][19][20]23 and home care [20][21][22] have also been used as indicators of quality end-of-life care.…”
Section: Strengths Limitations and Recommendationsmentioning
confidence: 99%
“…Receiving palliative radiation [16][17][18][19][20]23 and home care [20][21][22] have also been used as indicators of quality end-of-life care. Access to, and continuity of, primary care, the use of medical oncology and chemotherapy [18][19][20]22 , and being a nursing home resident 19,23,30 are also relevant. Socioeconomic and distance indicators of inequity should be investigated by linking the postal code of residence at death to census data 17,19,22,23,45 because a meta-analysis showed that the benefit from navigation is greatest for the most vulnerable individuals 46 .…”
Section: Strengths Limitations and Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations